A novel method to establish friction coefficient model for numerical simulation of inertia friction welding - Hao Wang; Guoliang Qin; Banglong Fu; Yuan Gao; Changan Li (Materials & Design, 2024)
The precise friction coefficient at interface determines the friction behavior in inertia friction welding (IFW), its model is the basis to precisely describe the friction behavior in the numerical simulation of IFW. To measure the friction coefficient related to the temperature, pressure, and sliding velocity, the IFW trials between 2219-O Al alloy and 304 stainless steel were conducted with the simultaneous measurement of temperature and angular velocity evolutions. Two types of friction coefficient models were established by considering whether the effects of temperature and friction pressure were independent. The S-(T&P) L model, which considered the couple effect of temperature and friction pressure, was recommended as the best suitable model with its very high accuracy and best simplicity. The proposed model was successfully used in simulating the temperature evolution of IFW between Al alloy and steel tubes. The effect of the influencing variables on the friction coefficient was also discussed.